Carbapenem-resistant hypermucoviscous Klebsiella pneumoniae clinical isolates from a tertiary hospital in China: Antimicrobial susceptibility, resistance phenotype, epidemiological characteristics, microbial virulence, and risk factors - Wang, Qiang; Chen, Mengyuan; Ou, Qian; Zheng, Lina; Chen, Xuejing; Mao, Guofeng; Fang, Jiaqi; Jin, Dazhi; Tang, Xiaofang (Frontiers in Cellular and Infection Microbiology, 2022)
Hypervirulent and multidrug-resistant Klebsiella pneumoniae poses a significant threat to public health. We aimed to determine the common carbapenemase genotypes and the carriage patterns, main antibiotic resistance mechanisms, and in vitro susceptibility of clinical isolates of carbapenem-resistant K. pneumoniae (CRKP) to ceftazidime/avibactam (CZA) for the reasonable selection of antimicrobial agents and determine whether hypermucoviscous (HMV) phenotype and virulence-associated genes are key factors for CRKP colonization and persistence. Antibiotics susceptibility of clinical CRKP isolates and carbapenemase types were detected. CRKP isolates were identified as hypermucoviscous K. pneumoniae (HMKP) using the string test, and detection of virulence gene was performed using capsular serotyping. The blaKPC-2, blaNDM, blaIMP, and/or blaOXA-48-like were detected in 96.4% (402/417) of the isolates, and the blaKPC-2 (64.7%, 260/402) was significantly higher (P<0.05) than those of blaNDM (25.1%), blaOXA-48-like (10.4%), and blaIMP (4.2%). Carriage of a single carbapenemase gene was observed in 96.3% of the isolates, making it the dominant antibiotic resistance genotype carriage pattern (P < 0.05). Approximately 3.7% of the isolates carried two or more carbapenemase genotypes, with blaKPC-2 + blaNDM and blaNDM + blaIMP being the dominant multiple antibiotic resistance genotype. In addition, 43 CRKP isolates were identified as HMKP, with a prevalence of 10.3% and 2.7% among CRKP and all K. pneumoniae isolates, respectively. Most clinical CRKP isolates were isolated from elderly patients, and carbapenemase production was the main mechanism of drug resistance. Tigecycline and polymyxin B exhibited exceptional antimicrobial activity against CRKP isolates in vitro. Furthermore, blaKPC-2, blaNDM, and blaOXA-48-like were the main carbapenemase genes carried by the CRKP isolates. CZA demonstrated excellent antimicrobial activity against isolates carrying the single blaKPC-2 or blaOXA-48-like genotype. Capsular serotype K2 was the main capsular serotype of the carbapenem-resistant HMKP isolates. Survival rates of Galleria mellonella injected with K. pneumoniae 1–7 were 20.0, 16.7, 6.7, 23.3, 16.7, 3.3, and 13.3, respectively. Therefore, worldwide surveillance of these novel CRKP isolates and carbapenem-resistant HMKP isolates as well as the implementation of stricter control measures are needed to prevent further dissemination in hospital settings.